T-cell deficiency and hyperinflammatory monocyte responses associate with Mycobacterium avium complex lung disease - Lindestam Arlehamn, Cecilia S.; Benson, Basilin; Kuan, Rebecca; Dill-McFarland, Kimberly A.; Peterson, Glenna J.; Paul, Sinu; Nguyen, Felicia K.; Gilman, Robert H.; Saito, Mayuko; Taplitz, Randy; Arentz, Matthew; Goss, Christopher H.; et al. (Frontiers in Immunology, 2022)
Immunological mechanisms of susceptibility to nontuberculous mycobacterial (NTM) disease are poorly understood. To understand NTM pathogenesis, we evaluated innate and antigen-specific adaptive immune responses to Mycobacterium avium complex (MAC) in asymptomatic individuals with a previous history of MAC lung disease (MACDZ). We measured MAC-, NTM-, or MAC/Mtb-specific T-cell responses by cytokine production, expression of surface markers, and analysis of global gene expression in 27 MACDZ individuals and 32 healthy controls. We also analyzed global gene expression in Mav-infected and uninfected peripheral blood monocytes from 17 MACDZ and 17 healthy controls. We were unable to detect increased T-cell responses against MAC-specific reagents in MACDZ compared to controls, while the responses to non-mycobacteria derived antigens were preserved. MACDZ individuals had a lower frequency of Th1 and Th1* T-cell populations. In addition, MACDZ subjects had lower transcriptional responses in PBMCs stimulated with a mycobacterial peptide pool (MTB300). By contrast, global gene expression analysis demonstrated upregulation of proinflammatory pathways in uninfected and M. avium-infected monocytes, i.e. a hyperinflammatory in vitro response, derived from MACDZ subjects compared to controls. Together, these data suggest a novel immunologic defect which underlies MAC pathogenesis and includes concurrent innate and adaptive dysregulation which persists long after completion of treatment.